Café turc ou cappuccino ? Pratiques de loisirs et distinction sociale dans les cafés cairotes - Florian Bonnefoi (EchoGéo)
Going to the coffeehouse is one of the most common and shared practices of leisure in Cairo among men. Coffeehouses are everywhere in the agglomeration: from the city-center to the periphery, from popular to upper-class areas. Though practices are quite the same, there are different types of coffeehouses between the ahwa baladî (popular street-coffeehouse), the coffee-shop and the café. Choosing one of them depends on spatial strategies related to neighborhoods and their reputations, and also on gender and class dynamics. Leaning on a two years long ethnographic fieldwork, this article shows how coffeehouses while being often criticized as places of idleness embody social distinction in Cairo.